2020
DOI: 10.1007/s00787-020-01586-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional impairment outcomes in clinical trials of different ADHD medications: post hoc responder analyses and baseline subgroup analyses

Abstract: Several recent phase 3 clinical trials of attention-deficit/hyperactivity disorder (ADHD) medications have used the Weiss Functional Impairment Rating Scale-Parent Report (WFIRS-P). Here, we assess WFIRS-P response in individual patients in two pivotal trials of lisdexamfetamine dimesylate (LDX) and guanfacine extended release (GXR). We also analysed pooled WFIRS-P data from seven phase 3 studies of ADHD medications to shed light on factors associated with baseline functional impairment. The proportion of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
3
6
0
Order By: Relevance
“…These results are consistent with the literature suggesting that oppositional defiant disorder (ODD), conduct, or internalizing symptoms may exacerbate impairment levels in children with ADHD, especially in the social domains (e.g. Bishop, Mulraney, Rinehart, & Sciberras, 2019;Coghill et al, 2006Coghill et al, , 2020Ros & Graziano, 2018;Wehmeier, Schacht, & Barkley, 2010). For instance, the level of social impairment tends to be heightened when symptoms of or comorbid ODD or conduct disorder co-exist with ADHD (Coghill et al, 2006;Wehmeier et al, 2010), and a meta-analytic review of social functioning found that the relationship between ADHD and social skills deficits (but not peer functioning) was weaker in studies adjusting for the influence of conduct problems than in studies failing to do so (Ros & Graziano, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with the literature suggesting that oppositional defiant disorder (ODD), conduct, or internalizing symptoms may exacerbate impairment levels in children with ADHD, especially in the social domains (e.g. Bishop, Mulraney, Rinehart, & Sciberras, 2019;Coghill et al, 2006Coghill et al, , 2020Ros & Graziano, 2018;Wehmeier, Schacht, & Barkley, 2010). For instance, the level of social impairment tends to be heightened when symptoms of or comorbid ODD or conduct disorder co-exist with ADHD (Coghill et al, 2006;Wehmeier et al, 2010), and a meta-analytic review of social functioning found that the relationship between ADHD and social skills deficits (but not peer functioning) was weaker in studies adjusting for the influence of conduct problems than in studies failing to do so (Ros & Graziano, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…In fact, our high‐end group selected from the continuum included 105 children who had a symptom severity at a level typically considered to be of clinical relevance (percentile ≥ 95) with ADHD‐RS‐IV scores of 28 and above – a threshold similar to that used as an inclusion criteria for clinical trials (e.g. Coghill et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, treatment with stimulants and nonstimulants can improve symptoms even in patients with very poor baseline functioning scores and can preclude the need for additional medications to control symptoms. 56,57 These findings are corroborated by articles identified in the present search, in which MTS improved symptoms of ADHD, PD, ODD, and ED in adult patients. 44,46,50 While some studies of MTS have included adults, amphetamine patch data are missing.…”
Section: Discussionsupporting
confidence: 81%
“…Studies in the present analysis reported that while dermal reactions tended to be worse with MTS compared with placebo, 25,44 the majority of erythema cases were mild and transient. In McRae-Clark et al, 45 57.1% of adult patients reported a skin reaction, a greater proportion of study subjects than was observed in any of the pediatric studies (n = 3, 1.3%-3.7%). 38,43,51 This difference may be partially related to small sample size, as McRae-Clark et al 45 included only 14 patients.…”
Section: Safetymentioning
confidence: 84%
“…In contrast to these results, a 13-week, double-blind, placebo-controlled RCT found that once-daily GXR (1–7 mg per day) did not improve the WFIRS-P LSP score in adolescents (13–17 years of age) with ADHD at Week 13 [ 12 ]. Coghill et al [ 13 ] reviewed two Phase 3 clinical trials of LDX and one of GXR and concluded that LDX was more effective than GXR in improving the WFIRS-P LSP score. LDX, however, was not more effective than OROS-MPH in improving the same score [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%